2009
DOI: 10.1021/jm900251a
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Small Molecule Glycerol 3-Phosphate Acyltransferase Inhibitors

Abstract: The incidence of obesity and other diseases associated with an increased triacylglycerol mass is growing rapidly, particularly in the United States. Glycerol 3-phosphate acyltransferase (GPAT) catalyzes the rate-limiting step of glycerolipid biosynthesis, the acylation of glycerol 3-phosphate with saturated long chain acyl-CoAs. In an effort to produce small molecule inhibitors of this enzyme, a series of benzoic and phosphonic acids was designed and synthesized. In vitro testing of this series has led to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 40 publications
2
54
0
Order By: Relevance
“…The mitochondrial GPAT assay has been described (39). As we have done previously (53)(54), isolated mitochondria were added to an incubation mixture with [ 14 C]glycerol-3-phosphate, palmitoyl-CoA, and varying concentrations of FSG67. For the current determinations, the assay was run with or without the sulfhydryl-reactive compound NEM (100 M) to distinguish the NEM-insensitive GPAT1 activity from that of NEM-inactivated GPAT2 (29).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mitochondrial GPAT assay has been described (39). As we have done previously (53)(54), isolated mitochondria were added to an incubation mixture with [ 14 C]glycerol-3-phosphate, palmitoyl-CoA, and varying concentrations of FSG67. For the current determinations, the assay was run with or without the sulfhydryl-reactive compound NEM (100 M) to distinguish the NEM-insensitive GPAT1 activity from that of NEM-inactivated GPAT2 (29).…”
Section: Methodsmentioning
confidence: 99%
“…An earlier evaluation showed that FSG67 had GPAT inhibitory activity in mouse mitochondria (53). We included NEM (100 M) to distinguish the activities of GPAT1 and GPAT2.…”
Section: Fsg67 Inhibits Both Gpat1 and Gpat2 Isoforms Of Liver Mitochmentioning
confidence: 99%
See 2 more Smart Citations
“…34 An insulin sensitizer 30 for the treatment of Type 2 diabetes has been reported. [35][36][37] Amongst these compounds, the most interesting is 29 (MK-0354) which has been the subject of many studies and structural modifications. [38][39][40] A compound for the treatment of ischemic stroke, 31 (a potent pan-JNK inhibitor) 41 and an inhibitor of coagulation to treat thromboembolic disorders 32 (inhibitor of factors IXa and XIa) 42 have been reported.…”
Section: Directly Linkedmentioning
confidence: 99%